ANALISIS PERENCANAAN STRUKTUR PERKERASAN KAKU PADA RUAS JALAN TOL JAKARTA-CIKAMPEK II SELATAN (STA 54+300 – 54+800) DENGAN METODE MDP 2017 - Andi Hidayat; Doni Haidar Nur; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
The main method of transportation to reach any traffic destination is the idea of roads. A road segment will achieve a level of safety and comfort if it is arranged according to the rules that have been set. The guidelines provided by the Public Works Agency for Toll Roads are guidelines commonly used in road planning in Indonesia. Heavy traffic on the Jakarta-Cikampek toll road is something that happens consistently, especially during peak hours, considering that this freeway is the main road that connects Jakarta with the surrounding areas. Therefore, Jasa Marga proposes to start the construction of the Cikampek 2 South Jakarta Toll Road. from Jatiasih Bekasi to Sadang Purwakarta are determined to reduce traffic congestion on these roads. The purpose of this final project is to calculate the traffic growth on the South Jakarta-Cikampek 2 toll road at a planned age of 40 years using the MDP2017 method, to calculate the thickness of the concrete slab that is produced when calculating the design age of 40 years using the MDP2017 method, and to calculate the diameter of the tie rods according to the MDP2017 provisions. With quantitative research methods whose activities include the stages of preparation, stages of data collection (primary and secondary), analysis of pavement thickness and comparing the conclusions. The results of the calculation of the cumulative load of the axle group are 61634116 or 6,2,E+07 at the design age of 40 years, while the calculation of the thickness of the concrete slab is 305mm, the LMC foundation layer is 100mm, Drainage layer is 150mm, and also produces a dowel diameter. by 3.8 mm Typical length 455mm with 305mm spacing.